Ornithine decarboxylase from mouse epidermis and epidermal papillomas: differences in enzymatic properties and structure. - O'Brien, T G (1986)
The properties of ornithine decarboxylase (OrnDCase) from mouse epidermis and benign epidermal tumors (papillomas) induced by the initiation-promotion protocol were compared. When crude extracts from each tissue were incubated at 55 degrees C, epidermal OrnDCase was rapidly inactivated, but the papilloma OrnDCase was more heat stable. Each of five individual papilloma extracts contained OrnDCase activity that was considerably more resistant to heat inactivation than was epidermal OrnDCase. Mixing of a papilloma and epidermal extract produced an intermediate heat-inactivation profile, suggesting that the differences in OrnDCase heat stability are not due to non-OrnDCase components of the extracts. Kinetic analyses indicated that the papilloma OrnDCase has an altered affinity for its substrate, L-ornithine, compared to epidermal OrnDCase. The apparent Km for L-ornithine for the epidermal enzyme was 0.07 mM while the Km values for the individual papilloma OrnDCases clustered around two higher values, 0.3 mM and 1.0 mM. The papilloma OrnDCases, but not epidermal OrnDCase, were activated by GTP and to a lesser extent by CTP. Immunoblot analysis showed the existence of multiple forms of OrnDCase in both epidermis and papilloma that differed in isoelectric point but not subunit molecular weight. None of the species of OrnDCase present in the epidermal extract coincided with the species present in papilloma. These results suggest that one consequence of neoplastic transformation in this in vivo system is the presence of an OrnDCase protein in benign tumors that differs structurally and functionally from the OrnDCase present in normal epidermis. The possible mechanisms responsible for these results and their significance for neoplastic development in this tissue are discussed.